(369) Statistical Laboratory Exercise Book - Mahmoud, M. W. (The Institute Of National Planning., 2018)
this exercise book is mainly intended for the members of the long term training course institute of national planning . it will also meet the needs of the students in the university who attend courses in statistics at any level.